RESPONS PERTUMBUHAN DAN PRODUKSI BAWANG MERAH (Allium ascalonicum L.) TERHADAP PEMBERIAN PUPUK NPK DAN Tithonia diversifolia (Hemsl.) Gray - Koko Elieser Ginting; Rosanty Rosanty Ratna; Hanum Hanum (Jurnal Agroekoteknologi, 2013)
Application of inorganic fertilizers continuously without the use of organic fertilizers has caused the degradation of agricultural land. The negative impacts caused by land degradation is a decline in agricultural yield, such as the yield of shallot. A solution to solve this problem is to combination inorganic with organic fertilizers exactly. So, the research was conducted to investigate combination of NPK fertilizer and Tithonia diversifolia on growth and production of shallot which is use Randomized Block Design with two factors. First factor is NPK fertilizer (0, 200, 400, 600 kg/ha) and the second factor is Tithonia diversifolia (0, 12500, 25000, 37500 kg/ha). The results showed that the treatment of NPK fertilizer  non significantly affect to all parameters and the highest production at dosage 400kg/ha (597,25 g/1,2m2). Tithonia diversifolia treatment non significantly affect to all parameters and the highest production at dosage 25000 kg/ha            (578,48g/1,2 m2). The interaction between the  NPK fertilizer and Tithonia diversifolia significantly affect to the shoot root ratio parameter.The highest shoot root ratio at treatment combination of NPK fertilizer at dosage 600 kg/ha and Tithonia diversifolia at dosage 12500 kg/ha(510,59).The highest production at treatment combination of NPK fertilizer at dosage 400 kg/ha and Tithonia diversifolia at dosage 25000 kg/ha (739,55 g /1,2 m2).   Key words: shallot, NPK fertilizer, Tithonia diversifolia